ALUMIMIUM-VEGETABLE COMBINATION TANNAGE FOR PRODUCTION OF SHOE UPPER LEATHERS (Journal of Veterinary Medicine and Animal Production, 2022)
Leather processing involves conversion of putrescible raw skins/ hides into useful material called leather by the process having common name ‘tanning’.Development of cleaner leather processing technologies is imperative for the sustenance of the tanning industry. In the present study, a combination tanning system based on Henna–Aluminum tannage for the production of upper leathers as a cleaner alternative is presented. Extract from the leaves of widely distributed lawsonia inerims (Henna) from Sudan has been evaluated for its tanning characteristics in a combination tanning system based on Henna and Aluminum sulphate. Both tanning methodologies henna followed by Aluminum (Henna-Al) and Aluminum followed by Henna (Al-Henna) have been attempted at concentration of 2% Al2O3. All combinations tanning systems resulted in leathers with shrinkage temperature above 90oC. However, Al-Henna leathers tanned using 2% Al2O3; followed by 20% hennaresulted in shrinkage temperature of 95oC, and Henna (20%) followed by Aluminum (2% Al2O3) resulted in leathers with shrinkage temperature of 97oC. The uptake of henna in Henna-Al tanning system with Henna (20%) followed by Aluminum (2% Al2O3) has been found to be better than the tanning system of Al-Henna. These leathers showed opened up, split compact fibre structure, indicating that the tanning process did not bring about any major change or destruction on the fibre structure of the leathers. The combination system provides significant reduction in the discharge of total dissolved solids in tanneries wastewater. Henna-Al combination system resulted in leathers with good organoleptic and strength properties. The work presented in this paper established the use of henna aluminium combination tanning system as an effective alternative cleaner tanning methodology.